Hypofractionated Radiation Versus Conventional Fractionated Radiation: A Network Analysis: Hypofractionated Radiation Versus Conventional Fractionated Radiation - Arjmand, Babak; Rezaei-Tavirani, Mostafa; Hamzeloo-Moghadam, Maryam; Razzaghi, Zahra; Khodadoost, Mahmood; Okhovatian, Farshad; Zamanian-Azodi, Mona; Ansari, Mojtaba (Journal of Lasers in Medical Sciences, 2022)
Introduction: Conventional fractionation (CF) and hypofractionation (HF) are two radiotherapy methods against cancer, which are applied in medicine. Understanding the efficacy and molecular mechanism of the two methods implies more investigations. In the present study, proteomic findings about the mentioned methods relative to the controls were analyzed via network analysis. Methods: The significant differentially expressed proteins (DEPs) of prostate cancer (PCa) cell line DU145 in response to CF and HF radiation therapy versus controls were extracted from the literature. The protein-protein interaction (PPI) networks were constructed via the STRING database via Cytoscape software. The networks were analyzed by “NetworkAnalyzer” to determine hub DEPs. Results: 126 and 63 significant DEPs were identified for treated DU145 with CF and HF radiation respectively. The PPI networks were constructed by the queried DEPs plus 100 first neighbors. ALB, CD44, THBS1, EPCAM, F2, KRT19, and MCAM were highlighted as common hubs. VTM, OCLN, HSPB1, FLNA, AHSG, and SERPINC1 appeared as the discriminator hub between the studied cells. Conclusion: 70% of the hubs were common between CF and HF conditions, and they induced radio-resistance activity in the survived cells. Six central proteins which discriminate the function of the two groups of irradiated cells were introduced. On the basis of these findings, it seems that DU145-CF cells, relative to the DU145-UF cells, are more radio-resistant.